Management of Iatrogenic Iridodialysis with Single-pass Four-Throw (SFT) Pupilloplasty : A Case Report: Poster Presentation - Case Report - General practitioner - Setiabekti, Nisia Pratama; Kristianto, Bobby (Majalah Oftalmologi Indonesia, 2023)
Introduction : Iridodialysis is a localized separation or tearing away of the iris from its attachment to the ciliary body. It occurs most commonly secondary to trauma, and it is more frequently associated with blunt traumas compared to penetrating eye injuries. Iridodialysis can also occur due to intraocular surgeries. The prevalence of iridodialysis secondary to blunt trauma was reported to be 9.3-14% as compared to 0.2% caused by cataract surgeries. Small and superiorly located iridodialysis may be left untreated. However, a more inferiorly placed, larger, or symptomatic iridodialysis warrants surgical repair. Case Illustration : A Male 62 years old came with chief complaint Glare on right eye after complicated cataract surgery 2 months before.Patient also complained blurry vison without redness. Examination found visual acuity 6/60 UCVA RE, iridodialysis at superior region from 10 o’clock until 1 o’clock, IOL (+) with good central, Normal Posterior Segment. Patient was treated with Single-pass Four-Throw (SFT) Pupilloplasty with local anesthesia and 1-month after Pupilloplasty we found visual acuity 6/30 UCVA RE and without any glare complaint anymore. Discussion : Management of this patient is a challenging case. The treatment og Single-pass Four-Throw (SFT) Pupilloplasty can give great outcome for visual acuity and glare symptom. SFT Pupilloplasty is also great and easy technique for beginner eye surgeon but for anesthesia, general anesthesia is more convenience than local ones. Conclusion : SFT Pupilloplasty is also great and easy techinique for iatrogenic iridodialysis.